2019
DOI: 10.4314/ahs.v19i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of paediatric emergency admissions and predictors of prolonged hospital stay at the children emergency room, University of Calabar Teaching Hospital, Calabar, Nigeria

Abstract: BackgroundThere is a high prevalence of paediatric emergency cases in less developed countries. However, prolonged hospital stay at emergency units may further overstretch the facilities.ObjectiveTo assess the patterns of presentations, services offered and predictors of a prolonged stay at the Children Emergency Room of a tertiary hospital in Southern Nigeria.MethodsThis prospective cross-sectional, study was conducted at the University of Calabar Teaching Hospital, Nigeria from 1st January–31st December 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
27
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 36 publications
10
27
8
2
Order By: Relevance
“…In our series, the pediatric emergency unit received patients until their stabilization. The average length of stay in the pediatric emergency room was 2.7 days (min-max: 1 -44 days), Enyuma et al reported a similar trend in their study in Nigeria [12]. In our series, the intensive care unit received patients until their stabilization.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In our series, the pediatric emergency unit received patients until their stabilization. The average length of stay in the pediatric emergency room was 2.7 days (min-max: 1 -44 days), Enyuma et al reported a similar trend in their study in Nigeria [12]. In our series, the intensive care unit received patients until their stabilization.…”
Section: Discussionsupporting
confidence: 75%
“…This result was similar to those found byNzame et al in Gabon, Ly Fatou in Senegal in 2016 and Asse et al, in Ivory Coast (2012). This was unlike results by Enyuma et al in Nigeria (2014) which had found a female predominance [8] [10] [11][12]. The mean age of the patients was 3.80 years, and children under 5 years of age accounted for 80.7% of patients.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…Além disso, um estudo ecológico que utilizou dados secundários dos SIH do território nacional evidenciou elevadas taxas de internação por lesões decorrentes de acidentes de transporte terrestre com predominância de pessoas do sexo masculino, residentes das regiões Centro-Oeste e Nordeste, com prevalência de jovens adultos, verificaram-se ainda que existe a possibilidade de homens terem maiores taxas de internações, pois se expõe mais a situações de risco por questões culturais (Andrade & Jorge, 2017). Na cidade de Calabar, Nigéria, um estudo avaliou os padrões de internamento hospitalar bem como o tempo de permanência em crianças admitidas no setor de emergência infantil em um hospital universitário da cidade de Calabar, e mostrou que houve uma proporcionalidade assimétrica quanto à idade, ou seja, crianças menores apresentavam tempo de permanência maior, evidenciando a média do tempo de permanência nesse hospital de 48 Development, v. 9, n. 8, e902986637, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.6637 horas, outro ponto relevante dessa pesquisa foi que o maior tempo de estadia estava relacionado a doenças infecciosas e que procedimentos cirúrgicos demandavam menor tempo de permanência hospitalar (Enyuma et al, 2019).…”
Section: Resultsunclassified
“…About a quarter of the admissions were due to fever, sickle cell anaemia and sepsis. The two later conditions were associated with prolonged hospital stay 11. Common causes of morbidity such as fever contributed the highest percentage of admissions.…”
Section: Child Healthmentioning
confidence: 98%